Comparison of dental health, treatment needs in visually impaired and normal healthy school-going children of 6–14-year age group - Sunil Kumar; Rishi Tyagi; Namita Kalra; Amit Khatri; Deepak Khandelwal; Dhiraj Kumar (Saudi Journal of Oral Sciences, 2020)
Introduction: This research aimed to evaluate and compare the oral health status and treatment required for visually impaired children and normal healthy school-going children in New Delhi and to investigate the factors that influence oral health. Subjects and Methods: The study was conducted in 420 children who were equally divided into visually impaired children and normal healthy children. Oral health status was recorded, which includes dental caries, plaque, debris, and gingival status in both groups. The Chi-square test was used, and statistical significance was fixed at (P < 0.05). Results: The total caries experience (Decayed, Missing, and Filled Surface + decayed, missing, filled surface) was found to be more in normal healthy children 2.72 than the visually impaired children 2.22 and it was found to be statistically significant (P < 0.05). Oral hygiene simplified index of normal healthy children and visually impaired children were 0.74 and 1.33, respectively, and found to be statistically significant (P < 0.05). The gingival index of normal healthy children was 0.10 found to be greater than visually impaired children 0.08. Visually impaired children required more treatment needs than normal healthy children. Conclusions: Visual impairment can actively limit these children maintaining good oral hygiene, and hence, it is important to create awareness, proper oral health guidance, and periodically screening to avoid complicated treatment needs in these children.